Intelligent Systems Technologies and Applications - Thampi, Sabu M.; Mitra, Sushmita; Mukhopadhyay, Jayanta; Li, Kuan-Ching.; James, Alex Pappachen; Berretti, Stefano; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book constitutes the thoroughly refereed post-conference proceedings of the third International Symposium on Intelligent Systems Technologies and Applications (ISTA'17), September 13-16, 2017, Manipal, Karnataka, India. All submissions were evaluated on the basis of their significance, novelty, and technical quality. This proceedings contains 34 papers selected for presentation at the Symposium.
A Color Image Segmentation Scheme for Extracting Foreground from Images with Unconstrained Lighting Conditions -- Automatic Diagnosis of Breast Cancer Using Thermographic Color Analysis and SVM Classifier -- Enhancement of Dental Digital X-Ray Images Based on the Image Quality -- MRI/CT Image Fusion Using Gabor Texture Features -- Face Recognition in Videos Using Gabor Filters -- Convolutional Neural Networks Based Method for Improving Facial Expression Recognition -- Composition of DCT-SVD Image Watermarking and Advanced Encryption Standard Technique for Still Image -- Performance Analysis of Human Detection and Tracking System in Changing Illumination -- Comparative Analysis of Segmentation Algorithms Using Threshold and K-Mean Clustering -- Semi-Supervised FCM and SVM in Co-Training Framework for the Classification of Hyperspectral Images -- Segmentation of Thermal Images Using Thresholding-Based Methods for Detection of Malignant Tumours -- Recognition of Handwritten Benzene Structure with Support Vector Machine and -- Logistic Regression a Comparative Study -- Image and Pixel Based Scheme for Bleeding Detection in Wireless Capsule Endoscopy Images -- Leaf Recognition Algorithm for Retrieving Medicinal Information -- Camouflaged Target Detection and Tracking Using Thermal Infrared and Visible Spectrum Imaging -- Heuristic Approach for Face Recognition Using Artificial Bee Colony Optimization -- ILTDS: Intelligent Lung Tumor Detection System on CT Images -- Blink Analysis Using Eye Gaze Tracker -- A Survey of Brain MRI Image Segmentation Methods and the Issues Involved -- Scene Understanding in Images.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence